Answer:
equidistant from point F and line d: (0, 3); (6, 6) and (-6, 6)
not equidistant from point F and line d: (3, 0); (3, 5) and (-2, 2)
Explanation:
Point (0, 3)
Distance from point (0, 6) = 3
Distance from line d = 3
Point (6, 6)
Distance from point (0, 6) = 6
Distance from line d = 6
Point (3, 0)
Distance from point (0, 6) = √[(3 - 0)² + (0 - 6)²] = √45
Distance from line d = 0
Point (3, 5)
Distance from point (0, 6) = √[(3 - 0)² + (5 - 6)²] = √10
Distance from line d = 5
Point (-2, 2)
Distance from point (0, 6) = √[(-2 - 0)² + (2 - 6)²] = √20
Distance from line d = 2
Point (-6, 6)
Distance from point (0, 6) = 6
Distance from line d = 6